EXPLORING THE CORRELATION BETWEEN PUPIL DISTANCE AND MYOPIA PREVALENCE: AN OBSERVATIONAL BIOANTHROPOLOGY STUDY IN SURABAYA - Kinasih, Anggitha Hayuning; Aditya, Dwi Martha Nur; Wicaksono, Y Adhimas Setyo (Folia Medica Indonesiana, 2025)
Bioanthropology integrates biological and cultural perspectives, thereby enhancing our understanding of human health across populations. Myopia is a significant refractive error affecting potentially 2.5 billion people globally by the end of the decade. Bioanthropological theories suggest that pupil diameter and distance contribute to axial elongation and the progression of myopia. Nevertheless, current literature lacks empirical validation through rigorous hypothesis testing, highlighting a gap in comprehension. The research explores the relationship between pupil distance and the incidence of myopia via empirical assessments in Surabaya. An observational cross-sectional study was conducted, which involved pupil distance measurements and eye refraction assessments. Inclusion criteria required participants to provide informed consent, while those with other specific refractive disorders were excluded. The research utilized a Pupillary Distance Meter for precise measurement of the pupil distance. In addition, the refractive index was assessed using standard ocular instruments, including the Snellen Chart, Trial Lens, Trial Frame, and Occluder tool sets. The research employed a non-probability sampling method with a consecutive design. The sample size was determined using the formula for proportion estimation. The data was analyzed using the Chi-Square (CI = 95%) statistical method. The study comprised 298 individuals as participants, of which 229 were from the adult population (124 emmetropic and 105 myopic), and 69 individuals were from the elderly population (47 emmetropic and 22 myopic). Based on gender, the sample consisted of 117 males (113 emmetropic; 4 myopic) and 181 females (58 emmetropic; 123 myopic). The study statistically discovered that there was no significant association between pupil distance and myopia prevalence, with a p-value <0.05 (0.933), indicating a lack of correlation. The empirical data analysis indicates no evidence linking pupil distance to myopia incidence. The incongruence between the empirical findings of the study and the theoretical construct suggests an indirect association via axial elongation, an association that requires further inquiry.